Determinants of Stock Prices: Evidence of Manufacturing Companies Listed on the Indonesia Stock Exchange - Deafatunnizwa Ulfida; Nadirsyah Nadirsyah; Ridwan Ibrahim (Universitas Syiah Kuala, 2021)
Objective – This study aimed to test and analyze the effect of the audit opinion, audit report lag, profitability, and leverage on stock prices in manufacturing companies listed on the Indonesian Stock Exchange (BEI) for the period of 2012-2018, either simultaneously or partially. Design/methodology – A total of 55 manufacturing companies were the samples of this study, and they were collected using a purposive sampling technique. Data analysis was conducted using multiple linear regression. Results – This study indicates that simultaneously audit opinion, audit report lag, profitability, and leverage can affect stock prices. Partially, auditing report lag and profitability calculated using ROA can affect stock prices. Meanwhile, audit opinion and leverage partially do not affect stock prices. Contribution – this study provides evidence on the factors influencing the stock prices specifically within the environment of listed manufacturing companies in Indonesia.